Self Assembly Gold Nanoparticles Modified Electrode For The Electrochemical Detection Of Mercury And Lead - Alaudin, Nur Asleena (Universiti Sains Malaysia, 2018)
AuNPs with 40 nm particle size were synthesized using the seeding-growth method. The synthesized AuNPs were characterized using X-ray Diffractometer, Zetasizer analysis, Scanning Electron Microscopy, UV-Visible Near-Infrared Spectrophotometer and Transmission Electron Microscopy. The produced AuNPs were used to self-assembled with the aid of Aminopropyltriethoxysilane (APTES) on ITO/PET electrode for the purpose of electrochemical detection of Hg(II) and Pb(II). The effects of several parameters were investigated for the electrochemical detection of Hg and Pb: the effect of APTES concentration, APTES soaking period, and AuNPs soaking period. The modified electrodes were subjected to cyclic voltammetry (CV) analysis to study the electrochemical behavior. SWASV analysis was performed on each parameter investigated in order to find the lowest limit of detection (LOD) value for Hg and Pb. The results showed APTES concentration of 1% gave the lowest LOD value among the other concentration which were 14.6 µg/L and 0.78 µg/L for Hg and Pb, respectively. Then, for the effect of APTES soaking period, 30 minutes soaking period gave the LOD value of 13.79 µg/L and 1.97 µg/L for Hg and Pb accordingly. Finally 6 hours of AuNPs soaking period gives the LOD value of 3.71 µg/L and 0.43 µg/L for Hg and Pb, respectively.